2021
DOI: 10.1164/rccm.202004-0993oc
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Exacerbations in Patients with Type 2 Diabetes and Asthma on Glucagon-like Peptide-1 Receptor Agonists

Abstract: Rationale: Glucagon-like peptide-1 receptor (GLP-1R) agonists are approved to treat type 2 diabetes mellitus and obesity. GLP-1R agonists reduce airway inflammation and hyperresponsiveness in preclinical models. Objectives: To compare rates of asthma exacerbations and symptoms between type 2 diabetic adults with asthma prescribed GLP-1R agonists and those prescribed sodium-glucose cotransporter-2 (SGLT-2) inhibitors, dipeptidyl peptidase-4 (DPP-4) inhibitors, sulfonylureas or basal insulin for diabetes treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 53 publications
3
69
0
Order By: Relevance
“…We read with interest the article by Albogami et al ( 1 ) on the association of glucagon-like peptide 1 receptor agonists (GLP-1RAs) and respiratory exacerbations among patients with asthma and/or chronic obstructive respiratory disease (COPD). In particular, the main conclusion that GLP-1RA initiation may be associated with a subsequent decrease in respiratory exacerbations echoes our findings recently published in the American Journal of Respiratory and Critical Care Medicine ( 2 ). Using electronic health records (EHR) of patients with asthma and comorbid type 2 diabetes, we found new initiators of GLP-1RAs had fewer asthma exacerbations than initiators of alternative step-up diabetes therapies in the 6 months following drug initiation.…”
supporting
confidence: 90%
“…We read with interest the article by Albogami et al ( 1 ) on the association of glucagon-like peptide 1 receptor agonists (GLP-1RAs) and respiratory exacerbations among patients with asthma and/or chronic obstructive respiratory disease (COPD). In particular, the main conclusion that GLP-1RA initiation may be associated with a subsequent decrease in respiratory exacerbations echoes our findings recently published in the American Journal of Respiratory and Critical Care Medicine ( 2 ). Using electronic health records (EHR) of patients with asthma and comorbid type 2 diabetes, we found new initiators of GLP-1RAs had fewer asthma exacerbations than initiators of alternative step-up diabetes therapies in the 6 months following drug initiation.…”
supporting
confidence: 90%
“…Subsequently, a recent retrospective cohort study demonstrated a reduction in number of asthma exacerbations in patients with T2D on GLP-1R agonists compared to other antiglycemic agents (comparative incidence rate ratio ranged 1.83-2.98) [17]. Findings were robust even when accounting for changes in hemoglobin A1c and BMI, concurrent metformin use, and exposures to other antiglycemic agents.…”
Section: Beyond Diabetesmentioning
confidence: 96%
“…In a recent retrospective cohort study, Foer and colleagues compared rates of asthma exacerbations and symptoms between patients with T2D and asthma prescribed GLP-1RAs and those prescribed sodiumglucose cotransporter-2 (SGLT-2) inhibitors, or DPP-4 inhibitors, or sulfonylureas, or basal insulin. They observed that patients prescribed GLP-1RAs had lower counts of asthma exacerbation and encounters for asthma symptoms after 6 months of the treatment (105). In another human study, Mitchell and colleagues reported that GLP-1R is expressed in both human eosinophils and neutrophils but the numbers were reduced in allergic asthmatics (106).…”
Section: Glp-1 Based Drugs In Lung Injury Studiesmentioning
confidence: 99%